2013
DOI: 10.1007/s12035-013-8408-8
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte N-Methyl-d-aspartate Receptor Signaling: Insights into Its Functions

Abstract: Myelination by oligodendrocytes facilitates rapid nerve conduction. Loss of oligodendrocytes and failure of myelination lead to nerve degeneration and numerous demyelinating white matter diseases. N-methyl-D-aspartate (NMDA) receptors, which are key regulators on neuron survival and functions, have been recently identified to express in oligodendrocytes, especially in the myelin sheath. NMDA receptor signaling in oligodendrocytes plays crucial roles in energy metabolism and myelination. In the present review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 144 publications
0
12
0
Order By: Relevance
“…NMDARs are indeed expressed in immature and mature oligodendrocytes. Activation of these receptors in oligodendrocytes modulates their metabolism, promotes their differentiation from immature into mature stage, and favors myelination around axons (Cao and Yao, 2013; Li et al, 2013). Interestingly, NMDAR activation promotes the differentiation of cultured oligodendrocytes via NOX-mediated ROS (Cavaliere et al, 2012).…”
Section: Oligodendrocytes/myelinationmentioning
confidence: 99%
“…NMDARs are indeed expressed in immature and mature oligodendrocytes. Activation of these receptors in oligodendrocytes modulates their metabolism, promotes their differentiation from immature into mature stage, and favors myelination around axons (Cao and Yao, 2013; Li et al, 2013). Interestingly, NMDAR activation promotes the differentiation of cultured oligodendrocytes via NOX-mediated ROS (Cavaliere et al, 2012).…”
Section: Oligodendrocytes/myelinationmentioning
confidence: 99%
“…Glutamate function is therefore an obvious therapeutic target in diseases involving white matter (57,256). However, white matter is home to glia-glia and glia-neuronal interactions mediated by most of the transmitters operating in grey matter, including glutamatergic, purinergic, GABAergic, glycinergic, adrenergic, cholinergic, dopaminergic, and serotonergic signaling (recent review in Ref.…”
Section: A Glutamate and Gabamentioning
confidence: 99%
“…Consistent with the OPC maturation promoting effects of D‐Asp through a mechanism involving the activation of both AMPA and NMDA receptors, it has been shown that glutamate signaling regulates both the initiation and completion of oligodendrocyte differentiation through the concerted activation of both these ionotropic glutamate receptors. In fact, whereas the activation of AMPA receptors regulates the early phase of OPC proliferation and initial differentiation, NMDA receptor activity regulates the morphological aspects of oligodendrocytes and the transition of immature to mature oligodendrocyte stage (Wake et al , ; Cavaliere et al , ; Cao & Yao, ; Li et al , ; Lundgaard et al , ; Martinez‐Lozada et al , ). Remarkably, the pivotal role played by these receptors in orchestrating OPC development is highlighted by recent studies showing that AMPA receptor signaling in oligodendrocyte lineage cells promotes OPC maturation and postnatal myelination by stimulating survival of newly differentiating oligodendrocytes (Kougioumtzidou et al , ), and blocking AMPA/kainate or NMDA receptors activity significantly inhibits remyelination (Li et al , ; Lundgaard et al , ; Gautier et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Wake et al, 2011;Cavaliere et al, 2012;Cao & Yao, 2013;Li et al, 2013;Lundgaard et al, 2013;Martinez-Lozada et al, 2014). Remarkably, the pivotal role played by these receptors in orchestrating OPC development is highlighted Effects of D-Aspartate treatment on corpus callosum remyelination.…”
mentioning
confidence: 99%